2015
DOI: 10.1007/s11596-015-1453-y
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype data of 23 Y-chromosome markers in Minnan Han Chinese and comparison with those of 12 Y-chromosome markers

Abstract: We genotyped 23 Y-STR loci (DYS576, DYS389I, DYS448, DYS389II, DYS19, DYS391, DYS481, DYS549, DYS533, DYS438, DYS437, DYS570, DYS635, DYS390, DYS439, DYS392, DYS643, DYS393, DYS458, DYS385a/b, DYS456, and GATA-H4) in a sample of 109 unrelated male Chinese people residing in Minnan area and compared the results with those from our previous study on 12 Y-STR. The haplotype diversity and the discrimination capacity of the 23 Y-STR reached 0.9903 and 0.9725, respectively, and the genetic diversity for each locus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Shui, Miao, She, Southern Han, Dai, Bai, Hakka Han, and Tibetan are dispersedly distributed in the MDS plot. Phylogenetic relationships among these 30 mainland Chinese populations 19 , 36 42 are visualized using the Neighbor-Joining tree (Fig. 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Shui, Miao, She, Southern Han, Dai, Bai, Hakka Han, and Tibetan are dispersedly distributed in the MDS plot. Phylogenetic relationships among these 30 mainland Chinese populations 19 , 36 42 are visualized using the Neighbor-Joining tree (Fig. 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the impact of investment, the study also revealed that delaying retirement and flexibly raising the individual contribution rate improved the replacement rate. Zhang and Lu (2021) pointed out that in calculating the life RROP, it was necessary to consider the life expectancy when determining the bookkeeping interest rate. Pu and Wang (2021) considered the difference of gender and constructed an actuarial model to calculate and analyze the retirement pension benefits of GDPI after the completion of occupational pension claims.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Steel Owing to the strong ability of deoxidization and desulphurization of rare earth, it have been used to treated spring steel. 108,135,[143][144][145][146][147][148] The recent advance research on the effect of rare earth modify inclusions in spring steel was done by professor Lai et al [136][137][138][139][140][141][142][143][144][145][146][147] They studied the effect of rare earth yttrium (Y) on inclusions in spring steel, the result indicated that Al 2 O 3 inclusions was transformed to YAlO 3 . In addition, the main inclusions are Y 2 O 3 , Y 2 O 2 S, Y 2 S 3 and the average diameter of inclusions decreased sharply after modified by rare earth yttrium (Y).…”
Section: Using Rare Earth To Modify Inclusions In Springmentioning
confidence: 99%